An Epidemiological Study of Road Traffic Accident Cases Attending a Tertiary Care Hospital - Bhandari, Binus; Shrestha, Sugam; Khadka, Dipendra (Journal of Nepalgunj Medical College, 2022)
Introduction: Road traffic accidents are a major global health problem. Incidence of road traffic accidents can be minimized by applying safety measures and following strict traffic rules and regulations. Aims: The main purpose of our study was to find out the socio-demographic profile of the victims involved in road traffic accidents and to provide epidemiological data. Methods: This is a hospital based, cross sectional study with victims of road traffic accidents attending to Nepalgunj Medical College, Kohalpur,a tertiary care center. Consecutive patients of road traffic accidents attending emergency department or admitted in wards (surgery, orthopedic or neurosurgery) were taken and information of injury pertaining to epidemiological factors and demographic profile along with time of occurrence of accident, type of vehicle involved, the pattern of injury, site of accident and part of body involved was collected on a pre-designed proforma. Results: Total patients enrolled in the study were 410.Majority of victims were young with age group of 10-19 years(18.5%). By gender male were more affected than female (67.8% versus 32.2%).Incident was more among married couple (61%). Majority belongs to Hindu by religion (96.1%). Regarding educational level majority have attained school level education (46.8%). By occupation majority were students (36.1%) followed by private employee (16.6%). Most of road traffic accidents were happened during summer season (65.4%). Regarding time most accidents were in between 6 PM10PM. Major site of accident was highway (63.4%). Among vehicle involved 4 wheelers were more common (65.4%).Head, neck and face region was found mostly injured in this study (33.2%). Most common type of injury was abrasion (30.7%) then followed by laceration (26.3%). Conclusion: Road traffic accidents can be minimized and it’s fatal consequences also preventable by strict enforcement of traffic rules and applying safety measures.